Dermatoglyphics in periodontics: An assessment of the relationship between fingerprints and periodontal status - A cross-sectional observation study - Prutha Vaidya; Swapna Mahale; Pallavi Badade; Ayushya Warang; Sunila Kale; Lavanya Kalekar (Wolters Kluwer Medknow Publications, 2017)
Context: Widespread interest in epidermal ridges developed only in the last several decades; however, it is still at infancy in the world of dentistry. The word "dermatoglyphics" comes from two Greek words (derma: Skin and glyphe: Carve) and refers to the epidermal skin ridge formations which appear on the fingers, palms of the hands, and soles of the feet. Aims: This study aims to assess the relationship between finger prints and chronic periodontitis. Materials and Methods: Two hundred patients were equally divided into chronic periodontitis and periodontally healthy group. The fingerprint patterns of the participants were recorded with a rolling impression technique using duplicating ink on executive bond paper. Statistical Analysis Used: The descriptive analysis of the data was presented as percentage frequency. The percentage frequencies of each pattern on each individual finger were calculated, and statistical tests were applied. Unpaired t-test was used for intergroup comparisons (P < 0.05). Results: There were statistically more whorls and less arches in both right and left hands in patients with chronic periodontitis. Conclusions: Dermatoglyphics can lead to early diagnosis, treatment, and better prevention of many genetic disorders of the oral cavity and other diseases whose etiology may be influenced directly or indirectly by genetic inheritance.